TAWURAN ANTAR PELAJAR DI JAKARTA SELATAN - Olav Rizky, Antonius; Zuryani, Nazrina; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This research tries to explain the student brawl phenomenon that happens in South Jakarta. researcher put South Jakarta as research site. In this research, researcher usesxconflictxtheory from LewisxA. Coser. Researcher usesxqualitativexresearch with descriptive method as methodology. The researcher gathered the data from observation, deep interview, and documentation. This research finds some findings as follows; there are some factors that start the brawl among senior high school students in South Jakarta like influence of gangster, chain of hostility that the students inherit from prior students, topographical condition in South Jakarta, and juvenile delinquency of each student; this research also finds the decreasing trend of student brawl in South Jakarta; and the existence of safety valve as a resolution of student brawl conflicts that happen among students. Many elements of the society that act as safety valve in this case are government, schools, police department, and parents. Keywords: Senior High School, Conflict, Students, Brawl